Utilization of the Anyflip Digital Library in Reading Comprehension Learning - Siti Sahara Ismail; Muslimin; Ayu Hidayanti Ali (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe: 1) the procedures for utilizing the Anyflip digital library in reading comprehension learning; 2) the reading comprehension learning outcomes through the utilization of the Anyflip digital library; and 3) the factors influencing students’ reading comprehension outcomes. This study was conducted at MTs. Negeri 2 Bolaang Mongondow Selatan during eight-grade students, with a sample of one class year. The population consisted techniques included observation, interview, and document anaylisis. The instruments of the study consisted of observation sheer, reading comprehension test question, and interview guideline. The reading comprehension assessment referred to the PIRLS indicators, which cover aspects such as locating explicit information, drawing inferences, integrating ideas, and evaluating content. Data were analyzed using a descriptive qualitative approach. The findings show that: 1) the prodecure for utilizing the Anyflip digital library was carried out in three stages; 5 initial activities, 3 core activities of the preparation stage, implemation stage, and evaluation stage, as well as 3 closing activities; 2) the average student reading comprehension scores were 79,54 in the first activity, 80,45 in the second activity, and 80,79 in the third activity; and 3) the factors influencing learning outcomes included students’ prior abilities, teks difficulty levels, infrastucture, internet acsess, and teacher assistance during the digital learning process.